Real-World Clinical Outcomes in Patients With HER2+ Metastatic Breast Cancer Receiving Tucatinib-Based Therapy After 2 or More Prior Metastatic HER2-Directed Regimens - Carey Anders MD; Edward Neuberger PharmD; Karen Bartley PhD; Brian T. Pittner PhD; Amadou Sow MD; Shu Wang PhD; Peter A. Kaufman MD (Cancer Control)
Introduction: Tucatinib is an oral human epidermal growth factor receptor 2 (HER2)-targeted therapy approved by the European Medicines Agency (EMA) for use in combination with trastuzumab and capecitabine for patients with HER2 + locally advanced or metastatic breast cancer (MBC) treated with ≥2 prior HER2-directed regimens. This real-world study describes patient characteristics and clinical outcomes with tucatinib after receiving ≥2 HER2-targeted therapies in the metastatic setting. Methods: This study included patients diagnosed with HER2 + MBC (between January 2017 and December 2022) who received tucatinib after ≥2 HER2-directed therapies in the metastatic setting in a US-based nationwide, de-identified electronic health record-derived MBC database. Patient demographic and clinical characteristics were captured at baseline (before tucatinib initiation). Outcomes assessed were real-world time to treatment discontinuation (rwTTD), real-world time to next treatment (rwTTNT), real-world overall survival (rwOS), and treatment persistence. Results: Of 3449 patients with HER2 + MBC, 89 received tucatinib, of which 30 received prior trastuzumab deruxtecan (T-DXd). Median (range) age of patients was 57 (30-84) years, 60.7% were White, and 66.3% had Eastern Cooperative Oncology Group performance status ≤1. Median (95% confidence interval) rwTTD was 5.9 (5.0-9.4) months, rwTTNT was 8.4 (6.2-11.8) months, and rwOS was 24.9 (15.6-not reached [NR]) months; in the post–T-DXd subgroup, these results were 6.4 (3.6-11.6), 6.4 (4.5-11.9), and 12.6 (11.9-NR) months. Treatment persistence was 43.9% (overall) and 33.3% (post–T-DXd) at 12 months and 15.4% at 24 months (overall). Conclusion: Tucatinib administered after ≥2 HER2-targeted therapies in the metastatic setting is an effective treatment option in patients with HER2 + MBC, including those treated with prior T-DXd.